A review on waste to biogas sources and its potential in Nigeria - Emeka Emmanuel, Okoro; Kevin C., Igwilo; E. Samuel, Sanni; Kale, Orodu (International Journal of Engineering and Technology, 2019)
Waste to biogas initiative is one major solution to the exponential increase of solid wastes in both rural and urban cities in Nigeria. This study examines the potential of producing organic waste materials for biogas and its benefits to the immediate councils where these organic waste are found in abundance. The choice of organic materials was based on reports from characterization from published literature. Based on this review, it was observed that researchers have been proposing a lot of unique approaches to manage solid waste generation. Most of their emphasis is towards perfect waste collection and disposal, but these approaches are very expensive considering the tight budget that the country is faced with. Various studies on this subject have been compiled from 2001 to 2017 and their outcomes and discoveries have been highlighted to show the importance of converting these organic wastes to biogas. The production and use of renewable energy sources are justified not only by energy, environmental and competitive aspects, but also on the aspect of rural development. These wastes have been identified in this study as huge sources of biogas which can be used to solve some of these council’s energy problems in their locality. This review also shows that new technologies are available to harness these opportunities; and the economic analyses done in some of the reviewed articles showed good payout periods when a large bio-digesters are used. This study showed that organic wastes are in abundance and at a very low cost, and the study further identified that some rural communities experience huge post-harvest organic wastes from their farms, thus, a good spot to start the implementation process for this initiative.